Kedudukan Penyandang Disabilitas pada Lembaga Keuangan di Indonesia: Subjek Hukum, Ahliyah dan Telaah KHES - Maulana, Diky Faqih (MUSLIM HERITAGE, 2023)
AbstractThe position of persons with disabilities as legal subjects is currently still being pros and cons due to obstacles that are considered as legal barriers. This paper will examine and analyze how far KHES is able to accommodate the position of persons with disabilities as legal subjects, especially when carrying out transactions at financial institutions. This research is a literature with a qualitative descriptive method with a normative juridical approach. The results of this study indicate that the status of ability to accept the law (ahliyah al-wujub), persons with disabilities are considered perfect people and there are no obstacles to receiving legal rights. However, to be competent to act legally (ahliyah al-ada'), the position of persons with disabilities must be adjusted to their ability to act legally. KHES has covered legal subjects, legal prowess and guardianship. However, it has not fully accommodated the legal provisions of the diversity of barriers for persons with disabilities. Article 4 KHES has explained that people who are incapable of carrying out legal actions are entitled to guardianship, in this case accommodating persons with disabilities with severe disabilities, and persons with mental and intellectual disabilities. In addition, Article 10 KHES also explains that guardianship permission can be stated in writing or orally. Article 12 KHES also explains the guardian's power as it comes into effect since the court's decision acquires permanent legal force. And in Article 13 KHES it is explained that the guardian is obliged to guarantee, protect the muwalla and his rights until he is capable of carrying out legal actions. AbstrakKedudukan penyandang disabilitas sebagai subjek hukum, saat ini masih menjadi pro kontra dikarenakan adanya hambatan yang dianggap sebagai penghalang cakap hukum. Tulisan ini akan mengkaji dan menganalisis seberapa jauh KHES mampu mengakomodir kedudukan penyandang disabilitas sebagai subjek hukum terutama saat menjalankan transaksional pada lembaga keuangan. Penelitian ini merupakaan kepustakaan dengan metode deskriptif kualitatif dengan pendekatan yuridis normatif. Hasil penelitian ini menunjukkan bahwa status kecakapan menerima hukum (ahliyah al-wujub), penyandang disabilitas termasuk orang yang sempurna dan tidak ada halangan untuk menerima hak hukum. Namun untuk cakap bertindak hukum (ahliyah al-ada’), kedudukan penyandang disabilitas harus disesuaikan dengan kemampuannya untuk bertindak hukum. KHES telah membahas subjek hukum, kecakapan hukum dan perwalian. Namun belum mengakomodir penuh secara ketentuan hukum dari keberagaman hambatan para penyandang disabilitas. Pasal 4 KHES telah menjelaskan bahwa orang yang tidak cakap melakukan perbuatan hukum berhak mendapat pewalian, dalam hal ini mengakomodir penyandang disabilitas dengan hambatan berat, dan penyandang disabilitas mental serta intelektual. Selain itu, pada Pasal 10 KHES juga diterangkan bahwa izin pewalian dapat dinyatakan secara tulisan atau lisan. Pasal 12 KHES juga menjelaskan kekuasaan wali sebagaimana yang mulai berlaku sejak penetapan pengadilan memperoleh kekuatan hukum tetap. Serta pada Pasal 13 KHES dijelaskan bahwa wali wajib menjamin, melindungi muwalla dan hak-haknya sampai cakap melakukan perbuatan hukum.